(untitled) (Academia Journal of Medicine, 2025)
Aim: The aim of the study is to compare the effect of pilates exercise and resisted muscle training of hip and knee joint muscles to improve pain and quality of life in tibio femoral osteoarthritis. Method: 50 patients diagnosed with tibiofemoral osteoarthritis were included in the study. The patients were randomly assigned into 2 groups. Group A received pilates exercise on mat for hip and knee joint muscle for 4 weeks and Group B received resisted muscle training using theratube for hip and knee joint muscle for 4 weeks. Pre and post intervention measures for KOOS (Knee Osteoarthritis Outcome Score) scale were observed and documented. Result & Conclusion: The results indicate that both group A and group B shows improvement in all components of KOOS. But when compared between both groups, group A shows more significant improvement in pain and symptom than group B.